WHO ICD-10 BASED ONLINE DISEASE DIAGNOSIS FOR GENERATING DIGITAL MEDICAL RECORD APPLICATION DEVELOPMENT - I Gusti Ngurah Lanang Wijayakusuma; Sagung Chandra Yowani (Prahasta Publisher, 2022)
Medical Record is a medical document that contain history of patient’s disease also information about given treatments and medicines. Diagnosis of patient’s disease is one of content in Medical Record. Public health office recommends medical facility to write diagnosis into ICD-10 WHO standard. However, there are many of medical facility translate diagnosis into ICD-10 WHO standard manually. This manual way will make a lot of mistake or wrong translate result. This research will develop an online application to help the doctor to write patient’s disease diagnosis into ICD-10 WHO automatically. Doctors need to type the keyword of diagnosis name then selected diagnosis will automatically write into ICD-10 WHO standard. This application also can generate Digital Medical Record that can help medical facility to reopen or save Medical Record Data in a long time.